Studi Makna Kosmologi Pada Hunian Tradisional Mamasa “Banua” - Maria Tara Kirana Anindita; Lintu Tulistyantoro (Intra, 2019)
Cosmology is the study of the universe (macrocosmos) in a concept of the relationship between the human world (microcosmos) and the universe. Banua is another name for the traditional house of Mamasa which has a deep meaning and philosophy, but is not widely known by the public. The purpose of this research is to learn the cosmological values of the traditional Mamasa residential “Banua” located in Rambu Saratu and Tondok Sirenden, Mamasa Regency, West Sulawesi. The method used in this study is a qualitative method with a participatory approach. The analysis technique was carried out comparing field data with a literature review of cosmology with the principle of dualism and pattern three. The results of the study indicate the existence of the principles of dualism and the three patterns implied in banua.